Bone marrow adipocytes. (3rd July 2017) - Horowitz, Mark C.; Berry, Ryan; Holtrup, Brandon; Sebo, Zachary; Nelson, Tracy; Fretz, Jackie A.; Lindskog, Dieter; Kaplan, Jennifer L.; Ables, Gene; Rodeheffer, Matthew S.; Rosen, Clifford J.
ABSTRACT: Adipocytes were identified in human bone marrow more than a century ago, yet until recently little has been known about their origin, development, function or interactions with other cells in the bone marrow. Little functional significance has been attributed to these cells, a paradigm that still persists today. However, we now know that marrow adipose tissue increases with age and in response to a variety of physiologic induction signals. Bone marrow adipocytes have recently been shown to influence other cell populations within the marrow and can affect whole body metabolism by the secretion of a defined set of adipokines. Recent research shows that marrow adipocytes are distinct from white, brown and beige adipocytes, indicating that the bone marrow is a distinct adipose depot. This review will highlight recent data regarding these areas and the interactions of marrow adipose tissue (MAT) with cells within and outside of the bone marrow.